The Administrative Law of Standardization in the PRC - Burke, Frederick R. (Columbia Journal of Asian Law, 1987)
In China, as in most other countries, there are official standards for a wide variety of industrial, agricultural, and commercial products, processes, testing methods, and measurement methods. All of these standards are “technological laws and regulations” and, as such, have a variety of legal ramifications. The number of official standards in China has increased dramatically over recent years and promises to continue to do so. These standards are incorporated by reference in a host of laws regulating everything from environmental protection to trade, technology transfer, and product liability. Although standards provide the touchstones for liability under the numerous laws and regulations which apply them, they are rarely set forth explicitly in those laws. Furthermore, although standards are not generally found in “internal documents” nor off limits to foreigners, they can be difficult to research and unpredictable in their application. Like the tip of an iceberg, these statutory references to standards provide an oblique clue to the extent of administrative law which lies below the surface of China’s legal system.